2011
DOI: 10.1128/iai.00451-10
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Staphylococcus aureus Biofilm Infection Using Vaccination and Antibiotic Treatment

Abstract: Staphylococcus aureus infections, particularly those from methicillin-resistant strains (i.e., MRSA), are reaching epidemic proportions, with no effective vaccine available. The vast number and transient expression of virulence factors in the infectious course of this pathogen have made the discovery of protective antigens particularly difficult. In addition, the divergent planktonic and biofilm modes of growth with their accompanying proteomic changes also demonstrate significant hindrances to vaccine develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 39 publications
1
111
0
1
Order By: Relevance
“…Antigens were chosen (glucosaminidase, an ABC transporter lipoprotein, a conserved hypothetical protein, and a conserved lipoprotein) because they are upregulated in biofilms both in vitro and in vivo. In a rabbit osteomyelitis model, the association of antibiotics and vaccination significantly increased the rate of therapeutic success (323). In that model, vaccination was initiated 30 days prior to the onset of infection, thus reducing the impact of the findings.…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigens were chosen (glucosaminidase, an ABC transporter lipoprotein, a conserved hypothetical protein, and a conserved lipoprotein) because they are upregulated in biofilms both in vitro and in vivo. In a rabbit osteomyelitis model, the association of antibiotics and vaccination significantly increased the rate of therapeutic success (323). In that model, vaccination was initiated 30 days prior to the onset of infection, thus reducing the impact of the findings.…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…Aside from vaccination aimed at preventing bacterial adhesion, it has also been suggested that vaccination will increase the likelihood of biofilm eradication (323). Antigens were chosen (glucosaminidase, an ABC transporter lipoprotein, a conserved hypothetical protein, and a conserved lipoprotein) because they are upregulated in biofilms both in vitro and in vivo.…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…This phenomenon of proteins with metabolic functions having antigenic potential has been observed in other immunoproteomic studies with P. acnes (9,38) and other Gram-positive pathogenic strains, such as S. aureus (27) and S. pyogenes (18). We focused our immunoproteomic analysis on cell wall-and membrane-associated proteins of P. acnes, since previous studies have shown that these proteins may be able to be used as novel diagnostic biomarkers or vaccine candidates (39). Our study might exclude secreted and/or cytosolic proteins (9) that are also important for biofilm pathogenesis and for the development of vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Such models have considerable utility in defining contributors to biofilm formation and therapeutic recalcitrance in vivo [15]. Moreover, animal models of biofilm infection facilitate therapeutic design, which is reflected by the creation of a multivalent vaccine that augments conventional antibiotic therapy to enhance clearance of biofilm infection [16].…”
Section: Modeling Of Biofilm Physiology and Chronic Osteomyelitismentioning
confidence: 99%